Prevalence and Antimicrobial Susceptibility Pattern of E. coli O157:H7 Isolated from Traditionally Marketed Raw Cow Milk in and around Asosa Town, Western Ethiopia - Nigatu Disassa; Berhanu Sibhat; Shimelis Mengistu; Yimer Muktar; Dinaol Belina (Veterinary Medicine International)
A cross-sectional study was conducted from October 2014 to July 2015 to determine the prevalence and populations of E. coli as well as the prevalence and antimicrobial susceptibility of E. coli O157:H7 isolated from raw milk. Biochemical and serological tests methods were used to confirm E. coli and E. coli O157:H7 and isolates were subjected to antimicrobial susceptibility test using the agar disc diffusion method. Out of 380 raw milk samples examined, 129 (33.9%) and 11 (2.9%) were contaminated with E. coli and E. coli O157:H7, respectively. The highest prevalence was recorded in samples obtained from vendors (39.1%, 4.978 ± 0.180 log10/ml) compared with samples from farmers (28.1%, 3.93 ± 0.01 log10/ml) with significant differences (P=0.02). The frequency of contamination was higher in the samples collected from milk that was stored and transported in plastic containers (39.4%) than in the containers made of stainless steel (23.0%) (P=0.002). The antimicrobial susceptibility profile showed that E. coli O157:H7 were resistant to tetracycline (81.8%), streptomycin (81.8%), and kanamycin (63.6%). Milk samples were produced and handled under poor hygienic conditions, stored, and transported in inappropriate containers and under temperature abuse conditions leading to high health risk to the consumers. Additional studies would be needed to establish association between the occurrences of E. coli O157:H7 in raw milk and all the risk factors involved in and around Asosa town.